On the suitability of additively manufactured gyroid structures and their potential use as intervertebral disk replacement - a feasibility study - Gross, Valentin; Zankovic, Sergej; Rolauffs, Bernd; Velten, Dirk; Schmal, Hagen; Seidenstuecker, Michael (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Intervertebral disk degeneration is a growing problem in our society. The degeneration of the intervertebral disk leads to back pain and in some cases to a herniated disk. Advanced disk degeneration can be treated surgically with either a vertebral body fusion or a disk prosthesis. Vertebral body fusion is currently considered the gold standard of surgical therapy and is clearly superior to disk prosthesis based on the number of cases. The aim of this work was the 3D printing of Gyroid structures and the determination of their mechanical properties in a biomechanical feasibility study for possible use as an intervertebral disc prosthesis.Material and methods: Creo Parametric 6.0.6.0 was used to create models with various Gyroid properties. These were printed with the Original Prusa i3 MK3s+. Different flexible filaments (TPU FlexHard and TPU FlexMed, extrudr, Lauterach, Austria) were used to investigate the effects of the filament on the printing results and mechanical properties of the models. Characterization was carried out by means of microscopy and tension/compression testing on the universal testing machine.Results: The 3D prints with the FlexHard and FlexMid filament went without any problems. No printing errors were detected in the microscopy. The mechanical confined compression test resulted in force-deformation curves of the individual printed models. This showed that changing the Gyroid properties (increasing the wall thickness or density of the Gyroid) leads to changes in the forcedeformation curves and thus to the mechanical properties. Conlcusion: The flexible filaments used in this work showed good print quality after the printing parameters were adjusted. The mechanical properties of the discs were also promising. The parameters Gyroid volume, wall thickness of the Gyroid and the outer wall played a decisive role for both FlexMed and FlexHard. All in all, the Gyroid structured discs (Ø 50 mm) made of TPU represent a promising approach with regard to intervertebral disc replacement. We would like to continue to pursue this approach in the future.